ANALYSIS OF STUDENTS' DIFFICULTIES IN SOLVING ALGEBRAIC OPERATION PROBLEMS BASED ON PROBLEM-SOLVING SKILLS IN GRADE VII AT SMP NEGERI 8 TAMBUN SELATAN - Mayawi Farida; Hotmaulina Sihotang; Candra Ditasona (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
This study aims to analyze the difficulties faced by students when solving algebraic operation problems based on the criteria of problem solving ability. This study was conducted to understand the factors that master students' difficulties in solving algebraic problems. This research used descriptive method with qualitative approach. The research subjects consisted of 35 students of class VII-G at SMP N 8 Tambun Selatan. Data were collected through observation, tests, questionnaires, and documentation. Data analysis used the Miles and Huberman data analysis model. Data validity was checked through method tringulation. The results showed that of the 35 students studied: 1) 61% of students had difficulty in understanding the problem, 2) 57% of students had difficulty in planning the solution, 3) 73% of students had difficulty in carrying out the plan, and 4) 86% of students had difficulty in checking back. The main factors that influence these difficulties are students' understanding of basic algebraic concepts, difficulties in applying mathematical concepts to the algebraic context and underdeveloped problem solving skills. In understanding math problems and formulating the steps needed to solve them, students often face difficulties.